A New Approach for Real Time Fault Diagnosis in Induction Motors Based on Vibration Measurement - da Costa, Cesar [UNESP]; Mathias, Mauro Hugo [UNESP]; Ramos, Pedro; Girao, Pedro Silva (IEEE, 2010)
Condition monitoring is used to increase machinery availability and machinery performance, reducing consequential damage, increasing machine life, reducing spare parts inventories, and reducing breakdown maintenance. An efficient real time vibration measurement and analysis instruments is capable of providing warning and predicting faults at early stages. In this paper, a new methodology for the implementation of vibration measurement and analysis instruments in real time based on circuit architecture mapped from a MATLAB/Simulink model is presented. In this study, signal processing applications such as FIR filters and fast Fourier transform are treated as systems, which are implemented in hardware using a system generator toolbox, which translates a Simulink model in a hardware description language - HDL for FPGA implementations.
Keywords: Rotating electrical machine; Fault; Condition monitoring; Diagnostic; Vibration; Digital signal processing; FPGA